Flexural behaviour of externally prestressed beams. Part I: Analytical model - Chee, Khoon Ng; Kiang, Hwee Tan (Elsevier Ltd., 2006)
Two features that distinguish an externally prestressed beam from an otherwise internally bonded, prestressed beam are: (i) the tendon stress depends on the overall deformation of the beam; and (ii) the tendons are free to move relative to the section depth, resulting in eccentricity variations defined as second-order effects. This paper presents a simple “pseudo-section analysis” method which accounts for second-order effects in simply supported, externally prestressed beams subjected to two symmetrically applied concentrated loads. The proposed method predicts the load–deflection curve and provides explicit expressions for the tendon stress, which can be used to evaluate the moment capacity of the beam by section analysis based on the bond reduction coefficient in strain compatibility.